Structure–function analysis of a new PL17 oligoalginate lyase from the marine bacterium Zobellia galactanivorans DsijT. (28th June 2021) - Jouanneau, Diane; Klau, Leesa J; Larocque, Robert; Jaffrennou, Agathe; Duval, Ghislain; Le Duff, Nolwen; Roret, Thomas; Jeudy, Alexandra; Aachmann, Finn L; Czjzek, Mirjam; Thomas, François
Abstract: Alginate is a major compound of brown macroalgae and as such an important carbon and energy source for heterotrophic marine bacteria. Despite the rather simple composition of alginate only comprising mannuronate and guluronate units, these bacteria feature complex alginolytic systems that can contain up to seven alginate lyases. This reflects the necessity of large enzyme systems for the complete degradation of the abundant substrate. Numerous alginate lyases have been characterized. They belong to different polysaccharide lyase (PL) families, but only one crystal structure of a family 17 (PL17) alginate lyase has been reported to date, namely Alg17c from the gammaproteobacterium Saccharophagus degradans . Biochemical and structural characterizations are helpful to link sequence profiles to function, evolution of functions and niche-specific characteristics. Here, we combined detailed biochemical and crystallographic analysis of AlyA3, a PL17 alginate lyase from the marine flavobacteria Zobellia galactanivorans Dsij T, providing the first structure of a PL17 in the Bacteroidetes phylum. AlyA3 is exo-lytic and highly specific of mannuronate stretches. As part of an "alginate utilizing locus", its activity is complementary to that of other characterized alginate lyases from the same bacterium. Structural comparison with Alg17c highlights a common mode of action for exo-lytic cleavage of the substrate, strengthening our understanding of the PL17 catalytic mechanism. We show that unlike Alg17c, AlyA3 contains an inserted flexible loop at the entrance to the catalytic groove, likely involved in substrate recognition, processivity and turn over.